Effect of Spirulina (Arthrospira platensis) Powder on The Physico-chemical and Sensory Characterization of Dry Noodle - Dinda Ersyah; Dwi Setijawati; Abdul Aziz Jaziri (Journal of Aquaculture and Fish Health, 2022)
Dry noodles are a staple food item among Asian population. Generally, it contains a low-fat and a high-carbohydrate level, however it lacks other nutrients, such as protein and dietary fiber. The addition of spirulina into dry noodles may increase both protein and dietary fiber. The aim of this study was to determine the effect of spirulina fortified in the dry noodle on physico-chemical and sensory properties. The method used in this study was experimental with a completely randomized design (CRD) using 4 replications. The spirulina powders added into dry noodles were 0%, 4%, 4.5%, 5%, 5.5%, 6% and 6.5%. The results showed the addition of spirulina in dry noodles had a significant effect (p<0.05) on nutritional values, such as protein, fat, ash, carbohydrate and dietary fiber. In addition, physical properties of fortified noodles, including cooking loss, elongation and tensile strength were also significant differences. For sensory attributes, noodles fortified with different concentrations of spirulina showed significant effects in appearance, aroma, color, taste and texture. A selected dry noodle fortified with 6% of spirulina based on the physico-chemical and sensory characterization. The fortified dry noodle can contribute to improving nutritional profile that may be beneficial on health.